Isoliquiritigenin Promotes the Repair of High Uric Acid‐Induced Vascular Injuries - Hongyan Zhou; Xinyu Song; Yingying Tian; Lili Zhao; Jingyi Yang; Fangfu Ye; Ting Cao; Jiayu Zhang (Smart Medicine)
ABSTRACT Hyperuricemia (HUA) is a chronic metabolic disease mainly stemming from purine metabolism disorders and strongly correlated with cardiovascular diseases, gout, chronic kidney disease, and other diseases. Elevated levels of uric acid (UA) in serum will lead to vascular endothelial cell injuries directly, subsequently impairing normal functions of human blood vessels. Therefore, investigating endothelial cell injuries resulting from HUA and corresponding drug screening for its treatment are of great significance in the prevention and treatment of vascular diseases. Given the inherent advantages of multiple targets and pathways, we delved into the potential of traditional Chinese medicine in alleviating vascular injuries induced by HUA in detail. Through the establishment of an injury index library and subsequent drug screening process, isoliquiritigenin proved to be a promising candidate for promoting the repair of HUA‐induced vascular injuries. It had been identified, validated and its efficiency evaluated using blood vessel‐on‐a‐chip and animal tests. Additionally, network pharmacology and molecular docking were further employed to elucidate the underlying mechanism. This work represents the first demonstration of isoliquiritigenin's capacity to facilitate the repair of vascular injuries triggered by high UA levels, and provides valuable insights for the treatment of HUA using traditional Chinese medicine.